Readiness For Organizational Change: Workplace and Individual Factors At PT TBK (JV Company) - Elfira Pipit Kurniawati; Sawidji Widoatmodjo (Pelopor Publikasi Akademika, 2023)
The merger & acquisition (M&A) process with foreign companies can cause changes in the company, ranging from changes in structure to processes and ways of working in the company. This study aims to determine the influence of workplace factors specifically organizational commitment, organizational culture, organizational support, and individual factors in the form of job satisfaction, work engagement and affective commitment to employee readiness to face change. Data for this study was gathered utilizing the probability sampling method, with a total of 156 respondents from the head office of PT Tbk. The findings indicate that organizational culture, organizational commitment, job satisfaction, work engagement, and individual commitment (affective commitment) significantly influence readiness for organizational change (p = 0.00). However, organizational support does not exhibit a statistically significant effect on readiness for organizational change (p = 0.053). Notably, organizational culture emerges as the most influential factor affecting readiness for organizational change.